Eating and Mealtime Behaviors in Vietnamese Children with Autism Spectrum Disorder: A Study Using the Brief Autism Mealtime Behaviors Inventory - Ha, Nguyen T.; Trang, Do Thi Hanh; Anh, Hoang K. T.; Ha, Le Thi Thu (Current Nutrition & Food Science, 2023)
Background: There has been an increase in the number of children with autism spectrum disorder (ASD), in whom problems with eating behaviors are often present. The use of a standardized questionnaire to assess the eating behaviors of children with ASD in Vietnam has not been paid due attention. Objective: This study aims to assess eating behaviors in children with ASD aged 3-11 years using the Brief Autism Mealtime Behaviors Inventory (BAMBI), thereby providing additional evidence to inform interventions in ASD children in Vietnam. Methods: An online survey using the BAMBI was conducted with parents of 85 children with ASD and parents of 175 typically developing (TD) children between April 2020 and April 2021. Results: The study revealed a higher risk of eating behavior problems among children with ASD compared to TD children (p < 0.0001). The differences between the two groups were statistically significant in 17 out of 18 items of the BAMBI. The study results also point out that in autistic children, the scores of 4/8 behaviors in the “limited variety” group were highest, which exceeded three points, while none of the behaviors relating to “food refusal” or “features of autism” reached three points. Conclusion: Future studies using direct observations with larger samples are needed to further investigate eating disorders among children with ASD.
Keywords: food refusal